If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) = 3x + -8 Reorder the terms: 4(-5 + x) = 3x + -8 (-5 * 4 + x * 4) = 3x + -8 (-20 + 4x) = 3x + -8 Reorder the terms: -20 + 4x = -8 + 3x Solving -20 + 4x = -8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -20 + 4x + -3x = -8 + 3x + -3x Combine like terms: 4x + -3x = 1x -20 + 1x = -8 + 3x + -3x Combine like terms: 3x + -3x = 0 -20 + 1x = -8 + 0 -20 + 1x = -8 Add '20' to each side of the equation. -20 + 20 + 1x = -8 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = -8 + 20 1x = -8 + 20 Combine like terms: -8 + 20 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 2(-4+a)=-24 | | 6x-7x=12 | | 8g+18=62 | | 2(3+k)=2 | | 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) | | 3c^2+25c+50=0 | | 11x-6=3x^2 | | 5=x+10 | | x^2-4x-21=fector | | x^4-4x^3-12x^2=0 | | 4/12= | | 5x+7.2=4x | | P^2+2p-8= | | 4x^2-24x+27=0 | | 5v^2+3=-8v | | w+16=-8 | | 3X+47=0 | | r^2+2rh-35h^2= | | 4x-5=7(x-5) | | 3x-4y=27 | | -19n=323 | | -(x+3)+2(x+7)= | | 3+5u=-27 | | 8s^2+4s= | | 8y-3=4y+15 | | 2x^2-14x+3=0 | | 14r=126 | | 6y+4x=44 | | 0=25x^2+7x-18 | | -3(x-4)-(2x-7)= |